Analysis of lightning activity characteristics and its relationship with precipitation in a strong convective weather process in Jiangsu Province - Mao, Yuqing; Liu, Jiao; Jiang, Youshan; Li, Cong; Han, Zhaoquan; Chen, Qu (Frontiers in Environmental Science, 2024)
Based on multi-source observation data such as lightning locator, atmospheric electric field instrument and hourly precipitation data from automatic stations, the lightning characteristics of the strong convective weather process under the influence of the northeast cold vortex in Nanjing Jiangsu Province on June 15, 2020 was analyzed in depth, and the relationship between the lightning activity and the precipitation was obtained. The results show that this strong convective weather process is formed by the cold air from the back of the northeast cold vortex along the front of the high-pressure ridge and the back of the transverse through southward to the middle and lower reaches of the Yangtze River, which makes the cold and warm air currents converge along the south of the Yangtze River to form the heavy precipitation , and is accompanied by the strong lightning activity in the process of this heavy precipitation. The local thunderstorm electric field in Nanjing is mainly characterized by negative increasing type, positive and negative alternating type, and multi-single thunderstorm electric field, and the thunderstorm activity is mainly dominated by negative ground flashes. During this strong thunderstorm, the stronger precipitation periods corresponded to the stronger lightning frequency periods, and the lightning and precipitation fallout areas showed a consistent spatial distribution. The correlation between the lightning activity and precipitation was analyzed by linear fitting, and the correlation between them is 0.946.